2008
DOI: 10.1111/j.1740-8261.2007.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Abdominal Radiographic Findings in Feline Cadavers

Abstract: Postmortem radiographic examinations of animals are commonly performed in judicial investigations to rule out gunshot and fractures. However, there was no available data on radiographic postmortem changes of animals. Forty-one sets of abdominal radiographs of feline cadavers made within 12 h of death were evaluated for postmortem changes. Intravascular gas was detected in 11 of 41 (27%) cadavers. The most common site of intravascular gas was the liver. Intravascular gas was also present in the aorta, femoral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
1
23
2
3
Order By: Relevance
“…A recent study on postmortem abdominal radiographs of feline cadavers performed within 12 h of death revealed the presence of intravascular gas in 27% of the cadavers [13]. The gas was detected in aorta, femoral artery, celiac and cranial mesenteric arteries, and caudal superficial epigastric artery, and also in the parenchyma of liver and spleen [13]. There were very few veterinary literatures on postmortem radiology [4,5,13].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent study on postmortem abdominal radiographs of feline cadavers performed within 12 h of death revealed the presence of intravascular gas in 27% of the cadavers [13]. The gas was detected in aorta, femoral artery, celiac and cranial mesenteric arteries, and caudal superficial epigastric artery, and also in the parenchyma of liver and spleen [13]. There were very few veterinary literatures on postmortem radiology [4,5,13].…”
Section: Introductionmentioning
confidence: 96%
“…In humans, postmortem CT had identified gas in the hepatic portal veins associated with gastrointestinal distension [14], in the cardiovascular system secondary to cardiopulmonary resuscitation [15] and in the mediastinum and soft tissue in cadavers of hanged persons [16]. A recent study on postmortem abdominal radiographs of feline cadavers performed within 12 h of death revealed the presence of intravascular gas in 27% of the cadavers [13]. The gas was detected in aorta, femoral artery, celiac and cranial mesenteric arteries, and caudal superficial epigastric artery, and also in the parenchyma of liver and spleen [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Heng et al (2008Heng et al ( , 2009) analysed the early stages of decomposition in cats and dogs by CT, but only over 8-24 hours. The authors observed and documented the development of intravascular and intrasplenic gases of putrefaction, at an ambient temperature of 22-33°C.…”
Section: Introductionmentioning
confidence: 98%
“…During the last decade, forensic radiographic examinations by computed tomography (CT) and magnetic resonance (MR) have led to a new approach, named Virtopsy (virtual autopsy), which is emerging as a non-invasive alternative to necropsy (Heng et al 2008). Only Heng et al (2008Heng et al ( , 2009) analysed the early stages of decomposition in cats and dogs by CT, but only over 8-24 hours.…”
Section: Introductionmentioning
confidence: 98%